Preparation of carbon-based AuAg alloy nanoparticles by using the heterometallic [Au4Ag4] cluster for efficient oxidative coupling of anilines. Issue 16 (12th April 2018) - Gao, Bin-Bin; Zhang, Min; Chen, Xu-Ran; Zhu, Da-Liang; Yu, Hong; Zhang, Wen-Hua; Lang, Jian-Ping
Abstract : A unique carbon-based AuAg alloy nanocomposite catalyst was prepared from the heterometallic [Au4 Ag4 ] cluster for efficient oxidative coupling of anilines. Abstract : We herein report the preparation of unique heteroatom-doped and carbon-based AuAg alloy nanoparticles (NPs) via the pyrolysis of a structurally defined octanuclear heterometallic Au(i )–Ag(i ) cluster [Au4 Ag4 (Dppy)4 (Tab)4 (MeCN)4 ](PF6 )8 (2, Dppy = diphenylphosphine-2-pyridine and Tab = 4-(trimethylammonio)benzenethiolate). This cluster-precursor approach exerts a fine control over the spatial arrangement, size and uniformity of the AuAg alloy NPs as well as the doped heteroatoms (P, N, F and S). The optimized material prepared at 450 °C efficiently catalyzes the oxidative coupling of anilines to yield azobenzenes under mild conditions.